Voices of letter in Greek phonosphere: study of chanting in Antiquity (Orfeu, 2019)
The historiography of Greek Antiquity presents music and language intimately associated. The metrical formulas presuppose mnemonic resources and suggest the correlations of aural paradigms and writing practices. Are there intrinsic aspects of Greek language that could shape melodic possibilities? The ancient conceptions about the music and poetry links are to be emphasized. How are structured the melody-text semantic resonances? How the rhythmic-melodic, semantic and performatic relations converge in chanting? The present article proposes to answer those questions by studying the singing-writing relation in the remaining Greek songs with ancient musical notation. The research of the musical rhythm, melody and poetic metrics associations reflects about vocal inflections that project specific ways of conceiving performance and composition. By the Humanistic Philosophy of Music (LIPPMAN, 2006) perspective, to understand the Greek vocality as a ritual manifestation will help us to interpret literomusical genres of Antiquity. It is thus possible to study the compositional practices and remnants of song performance, considering Greek vocality imbued with mythopoeic and cathartic meanings.
Keywords: Vocality; Musical-poetic genres; Aural composition